Ethnopharmacological importance of commonly used folk medicinal plants among the Malayali tribal community in Jawadhu Hills, Tamil Nadu, India: A review - Arul Raj , Moses Sam; Ayyanar, Muniappan (Ethnobotany Research and Applications, 2024)
Background: The Malayali tribal community residing in the hamlets of Jawadhu Hills in Tamil Nadu, India, is known for their exceptional knowledge of traditional medicine. This ethnobotanical review provides a comprehensive analysis of the diverse array of commonly used folk medicines used by Malayali tribals to address various health ailments and promote well-being using ethnomedicinal plants. Methods: An extensive investigation on key words ethnobotanical/ Jawadhu Hills/ Malayali tribe regarding literatures were collected for a period of 1990 to 2024 from various databases viz., PubMed, Google Scholar, DOAJ, Scopus, Web of Science, and Science Direct with search terms, Malayali tribes, Malayali tribals, tribes, Jawadhu hills, Javvadhu, ethnobotanical study, ethnobotanical survey, ethnobotanical explorations, and medicinal plants were used for the retrieval. Results: The present review reports a sum of 178 common traditional medicinal plants belonging to 69 families and 146 genera utilized by the Malayali ethnic community. The majority of the plants used are from the family Fabaceae, and they are used to treat various ailments. Conclusion: The folk medicinal plants recorded in the present report are identified with distinct and unique bioactive compounds responsible for various therapeutic effects. With this insight, herbal formulations from these plants can be prepared for vital usage and further suggested for the discovery of novel drugs in treating various diseases. Keywords: Herbal medicine, Jawadhu hills, Medicinal practitioners, Traditional knowledge Methods: An extensive investigation on ethnobotanical/ Jawadhu Hills/ Malayali tribe regarding literature was collected from 1990 to 2024 from various databases namely PubMed, Google Scholar, DOAJ, Scopus, Web of Science, and Science Direct with search terms, Malayali tribes, Malayali tribals, tribes, Jawadhu hills, Javvadhu, ethnobotanical study, survey, ethnobotanical explorations, and medicinal plants were used for the retrieval. Results: A sum of 178 common folkloric medicinal plants belonging to 69 families and 146 genera utilized by ethnic communities were documented in the present study. Among these, the majority of the plants are domesticated from the family Fabaceae for treating various ailments. Conclusion: The folk medicinal plants recorded in the present study are identified with distinct and unique bioactive compounds responsible for various pharmacological actions. With this insight, herbal formulations from these plants can be prepared for vital usage and further suggested for the discovery of novel therapeutic drugs.